Flood-Irrigated Soybean Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1998)
This publication projects a budget that reflects expected income and costs based on flood-irrigated soybean production.
MF577_1998_10
Keywords: MF577; Economics; Crops; MF